PREPARAÇÃO E CARACTERIZAÇÃO DE HIDROMEL UTILIZANDO DIFERENTES TIPOS DE MÉIS E TEMPOS DE FERMENTAÇÃO - Niemes, João Paulo (2013)
This work presents the development and optimization of methodologies for the production and characterization of mead, produced from different kinds of honey and by means of different fermentation times. Besides that, characterizations of pH, acidity, humidity, °B, ashes and humidity contents, by means of thermogravimetric analysis, and total reducing sugars content of the employed kinds of honey were realized, allowing comparisons among them, ascertaining the influence of their geographic origin. All, but the thermogravimetric analysis, of the aforementioned tests were also applied to the mead and the concentration of 5-HMF at the end of both short and long fermentation times was determined, with average values 0,210 ± 0,041 and 0,839 ± 0,198 μg.mLˉ¹, respectively. These values show that the beverage is within the international standards of quality regarding this parameter and show also that longer times lead to greater concentrations of this compound, due to the longer exposition of carbohydrates to a medium adequate to the dehydration of hexoses. The alcohol content obtained shows variations among long and short fermentation times, since in the last ones average values of 10°GL were obtained, versus 8,75°GL for the first ones. This shows that if higher alcohol contents are sought, longer fermentation times should be employed. The comparison among the prepared beverages was realized by means of sensory analysis, where the sensory profile of the samples and their acceptability to the consumer were assessed. The testers were previously trained, because it is still a not very well known beverage in the Brazilian consumer market. It was verified that the mead produced from a honey generally considered unsuitable for fresh consumption was the one most strongly appreciated by the testers, with a mead produced from a honey more suitable for fresh consumption coming in the second place. The experimental results obtained were subject to two-way ANOVA, with 95% confidence rate, to allow the comparison among the different prepared beverages. It was verified that the production of mead employing the proposed methodology is possible, with the advantage that this process, if executed correctly, preserves all the beneficial properties of the honey, unlike the traditional methodology. This is an excelling perspective for the regions of environmental protection, since bees intervene in the pollination of the flowers, and thus apiculture can be exerted in these areas. As honey production is mainly carried through by family farming, mead production may lead to better income distribution. This would allow to these families to remain in the countryside, avoiding rural exodus, for it stimulates the production of honey to supply the demand created by mead production and aggregates value to a product still barely consumed in our country.